Evaluation of development of bakeries of Crimea - Dunda, Svetlana (My University, 2012)
In the article the development of bakeries in two methods is evaluated.
Keywords: bread-making branch; хлібопекарська галузь; хлебопекарная отрасль; gold rule of economy; method by Petukhov; methods of non-parametric statistics; золоте правило економіки; методика Пєтухова; методи непараметричної статистики; золотое правило экономики; методика Петухова; методы непараметрической статистики; кафедра економіки праці та менеджменту